2012
DOI: 10.5897/ajpp11.227
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to metabolic monitoring guidelines in atypical antipsychotic treated subjects: Do physicians comply?

Abstract: Since the 1990s, the arrival of the new generation of antipsychotics, the atypical antipsychotics (AAP), heralded a new era in the management on psychotic patients as they are associated with much less side effects as the older drugs. However, the psychiatric community soon realized a new problem had emerged with these drugs, namely severe metabolic side effects. Several monitoring guidelines were soon published to guide treating physicians on how to deal with this issue. This study was aimed to assess adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Although all variables showed positive statistically significant findings, there is still a consistent gap between recommended practices and actual practices as found in previous studies (Bauer, 2002; Gill et al, 2012; Mitchell et al, 2012; Morrato et al, 2010; Pappadopulos et al, 2002). WC and family history are the two variables with the lowest adherence.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although all variables showed positive statistically significant findings, there is still a consistent gap between recommended practices and actual practices as found in previous studies (Bauer, 2002; Gill et al, 2012; Mitchell et al, 2012; Morrato et al, 2010; Pappadopulos et al, 2002). WC and family history are the two variables with the lowest adherence.…”
Section: Discussionsupporting
confidence: 81%
“…Although practice parameters and recommended screening guidelines are available, a discrepancy between best practices and actual practices has been shown (Gill, Tan, Lee, Tan, & Jawan, 2012; Morrato et al, 2010; Pappadopulos et al, 2002). In a literature review conducted by Bauer (2002), adequate adherence to guidelines was found 27% of the time in cross-sectional studies and in those studies looking at pre– and post–guideline implementations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since our results for overall monitoring compliance for major parameters showed similar array with the numbers reported in the literature, 3 we believe that the number of 38% reflects a real situation with follow-up monitoring period and is not merely a result of flawed study design ( Figure 2). As suggested by previous research, [8][9][10][11] we speculated several reasons for the lower compliance during the follow-up period. The most apparent one is that practitioners may not remember to order the tests on time due to the variable guideline requirements for each parameter at the specified intervals that make up the follow-up period.…”
Section: Discussionmentioning
confidence: 58%
“…Third, although the pattern of our results suggest that complexity or variability of the guidelines may be the major reason for decreased compliance, it may also be influenced by the factors described in previous reports as well. [8][9][10][11] Fourth, the monitoring percentages presented may be underestimated since our study did not capture data on services provided by outside PCP providers who have no access to BHMC EMR. The common practice in the clinic is to encourage patients to bring all recent outside laboratory reports, review them, and scan into the "Media" section in EPIC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation